1999
DOI: 10.1021/bi9906219
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Exchange between 5‘-Deoxyadenosine and Hydroxyethylhydrazine during the Single Turnover Inactivation of Ethanolamine Ammonia-Lyase

Abstract: The early steps in the single turnover inactivation of ethanolamine ammonia-lyase (EAL) from Salmonella typhimurium by hydroxyethylhydrazine (HEH) have been probed by rapid-mixing sampling techniques, and the destiny of deuterium atoms, present initially in HEH, has been investigated by mass spectrometry. The inactivation reaction produces acetaldehyde, the hydrazine cation radical, 5'-deoxyadenosine, and cob(II)alamin (B(12r)) in amounts stoichiometric with active sites. Rapid-mix freeze-quench EPR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…The most straightforward interpretation of the results regarding the onset of the 2 H KIE on reformation of coenzyme B 12 is that the only group being loaded with deuterium in experiments with unlabeled cofactor and deuterated substrates is the 5′methylene of the adenosyl moiety of the cofactor. This interpretation is consistent with results from studies of EAL with the single turnover inactivator, hydroxyethylhydrazine, which show that there is direct hydrogen exchange between the inactivator and 5′-deoxyadenosine without an intermediate carrier (40). Mass spectrometry was used previously to determine that the total pool (including the substrate) of exchangeable hydrogens in methylmalonyl CoA mutase was three (41).…”
Section: Resultssupporting
confidence: 76%
“…The most straightforward interpretation of the results regarding the onset of the 2 H KIE on reformation of coenzyme B 12 is that the only group being loaded with deuterium in experiments with unlabeled cofactor and deuterated substrates is the 5′methylene of the adenosyl moiety of the cofactor. This interpretation is consistent with results from studies of EAL with the single turnover inactivator, hydroxyethylhydrazine, which show that there is direct hydrogen exchange between the inactivator and 5′-deoxyadenosine without an intermediate carrier (40). Mass spectrometry was used previously to determine that the total pool (including the substrate) of exchangeable hydrogens in methylmalonyl CoA mutase was three (41).…”
Section: Resultssupporting
confidence: 76%
“…The presence of equimolar quantities of acetaldehyde and 5′-deoxyadenosine rules out multiple turnovers of HEH. Studies with [1,1,2,2-2 H 4 ]HEH, however, indicate that the first step is reversible (42). The HEH radical can eliminate the hydrazine cation radical leaving the enol of acetaldehyde (Scheme 2, path A) or rearrange to a product radical before fragmentation (Scheme 2, path B).…”
Section: Resultsmentioning
confidence: 99%
“…312,313 Hydroxyethylhydrazine (HEH), an analogue of 2-aminoethanol, has been found to be a mechanismbased inhibitor of EAL. 317,318 Incubation of EAL with excess AdoCbl and HEH leads to rapid loss (k ) 2.7 ( 0.3 s -1 ) of activity and the formation of about 6 equiv each of cob(II)alamin, 5′-deoxyadenosine, and acetaldehyde. Although earlier work had suggested that the R 6 β 6 EAL oligomer had two active sites, the stoichiometry of the reaction of EAL with HEH and AdoCbl indicates six active sites per molecule.…”
Section: Class II Eliminasesmentioning
confidence: 99%